PENGEMBANGAN BOOKLET TUMBUHAN ANGGREK ALAM SEBAGAI BAHAN AJAR PADA TOPIK PLANTAE UNTUK SMA/MA (Jurnal Bioconcetta, 2022)
This study aims to develop a booklet of types of natural orchids that are used as teaching materials on plantae material for junior high school students. The booklet contains pictures of the original types of orchids found in the Jorong Harapan Tinggam Community Forest, Talamau District, West Pasaman by describing the characteristics, morphology, classification, reproduction and role of orchids in life. The development of this booklet uses a 4-D model consisting of define, design, develop, and disseminate phase. The research carried out is only up to the develop stage, namely the validity test. This research was conducted in February 2022 at the PGRI Sumatera Barat University. The instrument used is a validity questionnaire, which be judged by of three validators, namely botanists, learning media experts and junior high school biology topics experts. The booklet validator includes three aspects of the assessment in terms of the feasibility of the content getting a score of 89%, the linguistic aspect is 87%, the didactic aspect is 86%, and the graphic aspect is 85%. The booklet that was developed as a whole got very valid results with a validation value of 86.75%.